Indikator Terpenting Dalam Keputusan Konsumen Berbelanja Online - Lemsina Kogoya; Ida Bagus Raka Suardana (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThis study aims to determine the influence of cultural factors on consumer behavior to shop online, the influence of social factors on consumer behavior to shop online, the effect of personal factors on consumer behavior to shop online. To determine the effect of psychological factors factors on consumer behavior to shop online. To know the influence of cultural factors on consumer decisions to shop online, the influence of social factors on consumer decisions to shop online, the influence of personal factors on consumer decisions to shop online, the influence of psychological factors on consumer decisions to shop online, and the influence of consumer behavior factor to consumer decision to shop online. The data were collected using questionnaires involving a sample of 114 people. Data analysis technique using SEM using AMOS application. The results showed the better the culture factor then the more supportive of consumer behavior with regression coefficient of 0.786. The better the social factors then the more supportive of consumer behavior with regression coefficient of 0.994. The better the personal factor then the more supportive of consumer behavior with regression coefficient of 0,518. The better the psychological factors then the more supportive of consumer behavior with regression coefficient of 0.214. The better the cultural factor the faster the consumer takes the decision with a regression coefficient of 0.648. The better the social factor the faster the consumer takes the decision with a regression coefficient of 0.404. The better the personal factor the faster the consumer takes the decision with a regression coefficient of 0.395. The better the psychological factor the faster the consumer takes the decision with a regression coefficient of 0.008. The better the consumer behavior the faster the consumer takes the decision with a regression coefficient of 0.190.